Answer:
Step-by-step explanation:
given that f(a) = K
we have the options of
f(K) = a
f ⁻¹ (K) = a
f ⁻¹ (a) = K
Where f ⁻¹ denotes an inverse function.
If f(a) = K, then its reciprocate, f ⁻¹ (K) = a
because it is essentially undoing the original equation
Step-by-step explanation:
from which text book please
The park is a total of 3+3 = 6 miles east of the mall, and 4+5=9 miles north of it. The Pythagorean theorem tells you the straight-line distance in miles is
√(6² +9²) = √117 ≈ 10.8
Answer:C
Step-by-step explanation: